Correction: A Survey of Availability and Affordability of Polypills for Cardiovascular Disease in Selected Countries - Gautam Satheesh; Bishal Gyawali; Marie France Chan Sun; Mark D. Huffman; Amitava Banerjee; Pablo Perel; Adrianna Murphy (Ubiquity Press, 2024)
This article details a correction to: Satheesh, G., Gyawali, B., Sun, M.F.C., Huffman, M.D., Banerjee, A., Perel, P. and Murphy, A. (2024) 'A Survey of Availability and Affordability of Polypills for Cardiovascular Disease in Selected Countries'. Global Heart. 19(1):p. 56. Available at: https://doi.org/10.5334/gh.1335.